TAMPIL MODIS DENGAN TOBACCO REJECT TEES - Falakh, Fajrul; Fitriyanto, Bagus; S P, Ramandhani Dwi; Rahmansyah, Hanif (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Smoking issue has become a major problem which need to adressed seriously by the Government, especially in Indonesia because smoking have killed millions of Indonesia children each years. The increase of smoking prevalence occurred in the age group15-24 years, from17.3% (2007) to 18.6% or increase almost 10 % in 3 years. The increase also occurred in the productive age group, that 25-34 years from 29.0% (2007) to 31.1% (2010). From these data it can be seen that most of teenagers are smoking. Adolescence is a period where a person wants to look fashionable. T-shirt is one of fashion trend which is much demand by teenagers. Above information make us innovate to open a business that also has a contribution in the control of smokers in Indonesia. We propose the effort of making T-shirts